Analysis of Indonesia’s Exports & Imports in the Asian Region: Before and During the Covid-19 Pandemic - Ngatno; Prihatiningsih, Apriatni Endang (Asian Economic and Financial Review, 2021)
The purpose of this study is to identify the impact of the Covid-19 pandemic on Indonesia’s export and import activity in the Asian region. Data on exports and imports from February 2019 to March 2020 (before the pandemic) and from April 2020 to May 2021 (during the pandemic) was collected from the Indonesian Central Statistics Agency portal. The results show that the impact of the Covid-19 pandemic does not always decrease Indonesia’s exports and imports in countries in the Asian region. For exports, out of 51 countries, only 18 decreased significantly, 14 countries decreased insignificantly, and 19 countries increased. On the import side, out of the same 51 countries, only 11 experienced a significant decline, 24 countries experienced an insignificant decrease, and 19 countries experienced an increase. The Indonesian government must implement various policies that can protect and encourage exports by providing fiscal stimulus, diversifying trading partners, deregulation, and industrial downstream, among others. Further research needs to be carried out on how the effects of the pandemic changed import and exports according to product type and how the severity of the pandemic affects within a country affected export and import activities.